New trends in software methodologies, tools and techniques : proceedings of the fourth SoMeT W05 - International Conference on New Trends in Software Methodologies, Tools and Techniques 2005 : Tokyo, Japan); Fujita, Hamido; Mejri, Mohamed, 1968- (Amsterdam ; Washington, D.C. : IOS Press, 2005)
This book presents a number of new trends and theories on the direction in which software science and engineering may develop to transform the role of software and science in tomorrow's information society. This is an attempt to capture the essence of a new state of the art in software science and its supporting technology. It also aims to identify the challenges such a technology has to master. The book comprises papers accepted at the fourth International Conference on New Trends in Software Methodologies, Tools and Techniques, held in Tokyo, Japan in September, 2005.
Chapter 8. Ubiquitous and web related systems software ; Meme media for the federation of intellectual resources over the web by clipping and combining them / Yuzuru Tanaka -- Component-based grid programming using the HOC-service architecture / Jan Dünnweber and Sergei Gorlatch -- Design and implementation of an agent-based middleware for context-aware ubiquitous services / Hideyuki Takahashi, Yoshikazu Tokairin, Takuo Suganuma, and Norio Shiratori -- Chapter 9. Software design for creative and interactive users ; Computation, interaction and imagination : into virtual space and back to reality / Ernest Edmonds and Linda Candy -- GUIDE : games with UML for interactive design exploration / Jennifer Tenzer -- A grounded theory study of programming in artist-programmer collaborations / Greg Turner, Alastair Weakley, Yun Zhang, and Ernest Edmonds -- Acting interactively in a digital world / Roman Danylak and Ernest Edmonds.
Includes bibliographical references at chapter ends, and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Software engineering -- Congresses; Expert systems (Computer science) -- Congresses; Artificial intelligence -- Congresses; Computer software -- Development -- Congresses; Génie logiciel -- Congrès.; Systèmes experts (Informatique) -- Congrès.; Intelligence artificielle -- Congrès.; COMPUTERS -- Programming -- Open Source; COMPUTERS -- Software Development & Engineering -- Tools; COMPUTERS -- Software Development & Engineering -- General; Artificial intelligence; Computer software -- Development; Expert systems (Computer science); Software engineering; Conference papers and proceedings